Applying the Prototype Model into the Electronic Reporting System for the Elementary School Student Base on Android - Tukino; Siti Masruroh; Daryanto Herdiana (Buana Information Technology and Computer Sciences (BIT and CS), 2021)
Teaching and learning is an activity that is bound by goal directed and carried out specifically to achieve that goal. Because it is very important to seek knowledge for a bright future. Supervision of students by the guardians of the students made the results of their children's achievements not improving. As well as student assessment by the teacher is still not well managed because it is still in the form of a note report. The system method used is the Prototype model. With observation and direct interviews with the student section regarding the assessment system in the school where the author researched. The results of this study are applications that can be operated on an Android Smartphone. This application can provide fast information and update automatically in obtaining information on student learning outcomes.